Expression and Functions of the CB2 Receptor in Human Leukocytes - Simard, Mélissa; Rakotoarivelo, Volatiana; Di Marzo, Vincenzo; Flamand, Nicolas (Frontiers in Pharmacology, 2022)
The cannabinoid CB2 receptor was cloned from the promyeloid cell line HL-60 and is notably expressed in most, if not all leukocyte types. This relatively restricted localization, combined to the absence of psychotropic effects following its activation, make it an attractive drug target for inflammatory and autoimmune diseases. Therefore, there has been an increasing interest in the past decades to identify precisely which immune cells express the CB2 receptor and what are the consequences of such activation. Herein, we provide new data on the expression of both CB1 and CB2 receptors by human blood leukocytes and discuss the impact of CB2 receptor activation in human leukocytes. While the expression of the CB2 mRNA can be detected in eosinophils, neutrophils, monocytes, B and T lymphocytes, this receptor is most abundant in human eosinophils and B lymphocytes. We also review the evidence obtained from primary human leukocytes and immortalized cell lines regarding the regulation of their functions by the CB2 receptor, which underscore the urgent need to deepen our understanding of the CB2 receptor as an immunoregulator in humans.